Towards a circular economy: The influence of extraction methods on phytosynthesis of metallic nanoparticles and their impact on crop growth and protection. Issue 5 (18th April 2022) - Rabalao, Tshegofatso M.; Ndaba, Busiswa; Roopnarain, Ashira; Vatsha, Banele
Abstract: The increasing food demand owing to aggressive population growth, accompanied by climate change‐related challenges necessitates new, eco‐friendly strategies for sustainable agriculture. Traditional inorganic fertilizers and pesticides for enhanced crop production are usually leached to waterways, leading to detrimental environmental health. Hence, the evolution of smart fertilizers or controlled release of agricultural ingredients is required to reduce and/or minimize leaching and maximize crop productivity. Smart fertilizers include engineered nanoparticles with a large surface area in comparison to their bulk counterparts. This beneficial property can increase soil fertility, crop productivity, and nutrient use efficiency. For a sustainable trajectory, cost‐effective and green synthetic methods for the preparation of such nanoparticles are urgently needed. Thus, research on the use of plant extracts as a green approach in the preparation of nanoparticles has largely increased over the years. Whilst several studies have been published on the green synthesis of nanoparticles, the extraction method in relation to nanoparticle quality has not been extensively explored. This review therefore provides the synthetic protocols of nanoparticles from the plant‐derived extracts and how plant extraction methods influence the morphology of the nanoparticles and thus their application for plant growth and protection.